2020
DOI: 10.1159/000505600
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Guided Internet-Delivered Cognitive Behavioral Therapy for Insomnia in General Practice: Results from a Pragmatic Randomized Clinical Trial

Abstract: <b><i>Introduction:</i></b> Guidelines recommend cognitive behavioral therapy for insomnia (CBT-I) as the first line of treatment for insomnia in general practice, but CBT-I is rarely available. Nurse-guided Internet-delivered CBT-I might be a solution to improve access to care. <b><i>Objective:</i></b> We aimed to determine the effectiveness of nurse-guided Internet-delivered CBT-I (I-CBT-I) on insomnia severity experienced by patients in general practice. <b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Second, it may be that patients, referred to iCBT-I directly from doctor's office, have active and more severe sleep complaints, and therefore are more motivated to benefit from the treatment (32,33,76,77). A lower dropout rate has previously been reported for an iCBT-I study conducted in primary care settings (75). These arguments let us rate recruitment in clinical settings as the key strength of the proposed study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, it may be that patients, referred to iCBT-I directly from doctor's office, have active and more severe sleep complaints, and therefore are more motivated to benefit from the treatment (32,33,76,77). A lower dropout rate has previously been reported for an iCBT-I study conducted in primary care settings (75). These arguments let us rate recruitment in clinical settings as the key strength of the proposed study.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, there is only one study of clinical effectiveness of iCBT for insomnia, in primary care, where patients were invited to participate in the study in two ways: during the general practitioner consultation or by means of the invitation letters referred to those patients who consulted for insomnia in the past year ( 75 ). Authors of this study report significant decrease of insomnia severity and improvement of sleep diary characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to evaluate the cost-effectiveness (outcome measures expressed in improvement in severity symptoms) and cost-utility (outcome measures expressed in Quality Adjusted Life Years; QALYs) of an internet-delivered CBT-I compared to care-as-usual for participants with insomnia treated in general practice from a societal perspective. Van der Zweerde et al recently showed that this guided, internet-delivered CBT-I resulted in greater improvements in insomnia severity compared to care-as-usual both at post treatment and at 26 weeks follow-up (Van Der Zweerde et al, 2020). We expected that the internet-delivered intervention would not only reduce insomnia severity, but also societal costs, while improving quality of life as compared to care-as-usual.…”
Section: Introductionmentioning
confidence: 90%
“…A clinically relevant response was defined as a change of ≥ 8 points in ISI score from baseline to follow-up (26 weeks) (Morin et al, 2011). The effectiveness outcomes for both i-Sleep and care-as-usual are extensively described in the clinical trial paper by van der Zweerde et al (Van Der Zweerde et al, 2020).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Therefore, we have used available datasets that cover different patient groups and psychological interventions. The selected sample consisted of data from RCTs on guided internet delivered cognitive behavioural treatment (CBT) for insomnia in the general population with [ 14 ] and without [ 15 ] elevated depressive symptoms, an RCT on meaning-centered group psychotherapy targeting personal meaning for cancer survivors [ 16 ], and from an RCT on guided internet-based CBT treatment for persons with diabetes with elevated depressive symptoms [ 17 ]. All these RCTs indicated that the interventions are effective with medium to large effect sizes using conventional analyses, e.g.…”
Section: Introductionmentioning
confidence: 99%